On the thermoelastic problem of uniform heat flow disturbed by a circular rigid lamellate inclusion (Archives of Mechanics - Test, 2009)
A complete solution in elementary functions is given for the three-dimensional thermoelastic ï¬eld in an elastic space, containing an absolutely rigid circular inclusion (anticrack) under a normally incident uniform heat ï¬‚ow. The inclusion is assumed to be slightly conducting, with a certain thermal resistance. The analysis is based on the potential theory method. The resulting boundary-value problems are reduced to classical mixed problems of the potential theory. The temperature, ï¬‚uxes, thermal stresses and displacements in the inclusion plane are given in closed forms and interpreted from the point of view of the failure theory.